2017
DOI: 10.1038/ncomms14085
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling exceptional acetylene and carbon dioxide adsorption within a tetra-amide functionalized metal-organic framework

Abstract: Understanding the mechanism of gas-sorbent interactions is of fundamental importance for the design of improved gas storage materials. Here we report the binding domains of carbon dioxide and acetylene in a tetra-amide functionalized metal-organic framework, MFM-188, at crystallographic resolution. Although exhibiting moderate porosity, desolvated MFM-188a exhibits exceptionally high carbon dioxide and acetylene adsorption uptakes with the latter (232 cm3 g−1 at 295 K and 1 bar) being the highest value observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(110 citation statements)
references
References 46 publications
4
105
1
Order By: Relevance
“…Obviously, there is a broader distribution for the S acc compared with the results shown in Figures a, b, and accessible surface areas covers a range of 2000–3800 m 2 /g among the materials with remarkably high C 2 H 2 uptakes. Because the open metal sites play a key role in enhancing the C 2 H 2 storage amount of MOFs, many studies have also used the density of Cu‐OMS in MOFs as a descriptor when comparing different materials . As can be seen from Figure d, higher volumetric density of Cu‐OMS will not necessarily lead to higher adsorption amount, and the optimal values can be considered within the range of 2.1–4.5 mmol/cm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, there is a broader distribution for the S acc compared with the results shown in Figures a, b, and accessible surface areas covers a range of 2000–3800 m 2 /g among the materials with remarkably high C 2 H 2 uptakes. Because the open metal sites play a key role in enhancing the C 2 H 2 storage amount of MOFs, many studies have also used the density of Cu‐OMS in MOFs as a descriptor when comparing different materials . As can be seen from Figure d, higher volumetric density of Cu‐OMS will not necessarily lead to higher adsorption amount, and the optimal values can be considered within the range of 2.1–4.5 mmol/cm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, disagreement on the role of amide functionalization in MOF gas adsorption exists in the literature. Theoretical results suggested that adsorption occurs at the carbonyl of the amide, while experimental studies indicated the amine as the adsorption site . Using SSNMR spectroscopy, XRD and DFT calculations, the adsorption site of Cu(INAIP), an amide‐functionalized MOF, was determined (Figure ) .…”
Section: Light Hydrocarbonsmentioning
confidence: 99%
“…Theoretical results suggested that adsorption occursa tt he carbonyl of the amide, [38] while experimental studies indicated the amine as the adsorption site. [39] Using SSNMR spectroscopy, XRD and DFT calculations, the adsorption site of Cu(INAIP), an amide-functionalized MOF,w as determined ( Figure 5). [36] For C 2 H 2 guests, single crystal (SC) XRD revealed one unique adsorptionsite at low temperatures.…”
Section: Light Hydrocarbonsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are one of the most highly porous materials and since their discovery, have been thoroughly investigated as a result of their specific properties that are exceptional among known materials . They combine two disciplines, namely organic and inorganic chemistry and possess many favorable characteristics, for example high surface area, high porosity, tenability, reproducibility, high sorption capacities, facile syntheses, and good possibilities for scale up .…”
Section: Introductionmentioning
confidence: 99%